Aquatic space activities - Practice needs theory - Ungerechts, B. E.; Klauck, J. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: Swimming is an aquatic activity of long history and so is the swimming research. The cause for being moved by selfinduced propulsion is traditionally confined to flow physics with experiments under steady conditions assuming that the flow velocity is constant and the moving body is a) rigid and b) fully submerged. In human swimming this is not and was never the case. Fact is, in all aquatic space activities limbs change motion of water mass which cause unsteady flow conditions. METHODS: A surway was done concentrating on chapters of some swimming text books related to biomechanical background of activities in aquatic space. Emphasis was placed on examples referring to studies presented in the congress series of biomechanics and medicine in swimming. In addition, attention was paid to which extend those hydrodynamic features examined by researchers of fast swimming animals were considered and how practical advice and biomechanical knowledge was connected. RESULTS: Most textbooks on swimming prefer simple drag approach. The authors emphasize the intuition about flow condition, e.g. a hand is moving the same block of water either back or moving new blocks by changing hand motion, ignoring that in a current flow, according to the law conservation of mass, water cannot be pushed away in relation to the surrounding water mass. This means among others, hands` actions are not most effective if water resistance is at a maximum. Even when the effect of hand motion has been jugded by analyzing the lift and drag components of hand the connection to known intracyclic changes of the swimming velocity is not mentioned. The question, where the mass of water displaced by the body and its actions is going to is not considered. CONCLUSION: Reactions to induced water mass set into motion have some contra-intuitive features. Studies of flow physics of swimming animals suggest that water mass displaced by the body is potentially supporting thrust production of the action of the feet. In aquatic space it is important to know the relation of peaks between added forces and accleration of body. When water mass is displaced by the hand in form of a vortex ring thrust will surely be enhanced remarkably. Momentum variations or flow unsteadiness due to hand motion generate efficient resultant propelling force. A change in teaching strokes is recommended.